Penerapan Latihan Drill Dalam Peningkatan Hasil Belajar Passing Bawah Bola Voli - Rifki Nur Ramadhan; Purno Darmanto; Cahyo Yuwono (Universitas Negeri Semarang, 2024)
The problem studied in this classroom action research is how to improve the basic technical skills of the bottom pass of the volleyball game through the drill method in class X-11 for the 2023/2024 academic year at SMA Negeri 11 Semarang. This research aims to improve volleyball bottom pass learning outcomes, namely through the application of volleyball bottom pass drill training. This research is classroom action research consisting of 2 cycles. The subjects in this research were class X-11 students at SMA Negeri 11 Semarang with a total of 36 students. The instrument used is the volleyball bottom pass performance test. The data obtained is in the form of skills learning results, observation sheets and documentation. The research results obtained in the form of student learning outcomes in cycle I were 58.3% or 21 students who had achieved the KKTP, while in cycle II the percentage increased to 83.3% of students who had achieved the KKTP. The conclusion of this research is that after using the drill method learning, it can improve the ability of the basic lower pass technique of volleyball in class X-11 students at SMA Negeri 11 Semarang in 2023/2024. Variation on foot step are required to make the tehcnique in volleyball passing more deeply apply